Enhancing sustainable intensification in Ethiopia through landscape restoration interventions: The sustainable intensification assessment framework approach - Adimassu, Zenebe; Tibebe, Degefie; Tamene, Lulseged; Abera, Wuletawu; Ayehu, Getachew Tesfaye (Elsevier, 2025)
Assessing the effects of landscape restoration interventions requires a systematic assessment approach that integrates Sustainable Intensification (SI) indicators. The Sustainable Intensification Assessment Framework (SIAF) is an impact assessment approach that incorporates SI indicators including productivity, economic, environmental, human and social conditions in the assessment of the performance of landscape restoration interventions. This study was conducted in the Geda and Doyogena landscapes of Ethiopia to assess the performance of landscape restoration interventions. The SIAF was used in two landscapes of Ethiopia. This paper employed various data sources including primary data from the Rural Household Multi-Indicator Survey (RHoMIS), secondary data from a literature review and satellite imagery. Remote Sensing and Geographical Information System (GIS) techniques were used to analyze satellite images while SPSS (V. 26) package was used to analyze primary survey data. Results showed that restoration in both landscapes improved the Normalized Difference Vegetation Index (NDVI), increased water productivity and reduced soil erosion. Although landscape restoration reduced soil erosion, it is still by far higher than the tolerable soil loss limit in the Doyogena landscape. This indicates that more land management interventions should be implemented in the coming years. We observed high variability of indicator scores across the five domains in both landscapes. The aggregated indicators showed that landscape management contributed to restoring the environment and improving agricultural productivity and income of households in Ethiopian highlands.